Fund Collection through Litigation by the State Treasury in the Roman Empire (with Special Reference to the First Three Centuries A.D.) - Dyjakowska, Marzena (Studia Ceranea, 2012)
The paper discusses the confiscation of property (publicatio bonorum) as a source of revenue for the fiscus in ancient Rome. The term fiscus means, among other things, the public property, State funds, but also the private property of emperors. The confiscated property could be adjudged not only to aerarium – the State Treasury (publicare), but also to the personal treasury of emperors, and trials seem to have been inspired to supply it. The most „successful” accusation was connected with the crime of lese-majesty: the scope of this crime was especially wide and it was easy to convict the defendant. The Senate often voted for adjudgement of the confiscated property in respect of the Emperor, especially if the convict had received some benefits from him. This practice turned into a rule and the Emperor’s treasury became the sole beneficiary of publicatio bonorum. Some emperors are especially known as rulers accumulating their private property on confiscated goods (Caligula, Septimius Severus, Domitian). A portion of those goods was due to the children of the defendant; some rescripts issued by the emperors even ordered to transfer his whole property in the first place to his descendants. In spite of the rule that it was necessary to find the defendant guilty to confiscate his property, the publicatio bonorum was not available; when he committed suicide before the sentence, a presumption was made that this act was equal to a guilty plea. According to another rule – confessus pro indicato est – the defendant was convicted unless his suicide was justified. The personal belongings (pannicularia) were to be confiscated, too, but only after the conviction.